Projeto de atuadores robóticos aplicados a uma órtese de membro superior - Guilherme de Paula Rúbio (2020)
This master’s thesis presents the design, analysis and test of robotic actuators applied to an upper limb orthosis, used in the post stroke individuals rehabilitation, developed by the Bioengineering Laboratory of the Federal University of Minas Gerais. The Stroke is a common disease that affects countless people in Brazil and worldwide, resulting in upper limbs sequelae. Therapy techniques are used to try to restore the limb mobility to these people. Among of them, the robotic therapy has been showing the ability to rehabilitate these individuals in a satisfactory manner. For this, the development of the actuators used in this type of device is principal point to improve and optimize this therapy. This work shows the design of two actuators that perform finger opening and elbow flexion and extension. The design and selection of artificial tendons using a tensile strength test is shown, as well as the design of a power screw that pulls and relaxes the cables of this actuation mechanism. In the elbow actuator, a mechanism was design to generate an output torque of 12 Nm, as well as the structure simulations used to support the actuator and prevent involuntary pronation performed during elbow flexion. To trigger the actuators, a triggering system using limit switches, encoder and a microcontroller was developed. Finally, a test was carried out with an post stroke individual, analyzing the movement capacity that is reached by the device. With the tensile strength tests, a DuPont TM Kevlar R rope was selected as an artificial tendon. A power screw with 12 mm in diameter, 3 fillets and 2 mm pitch was used as a artificial tendon traction system. A four bar mechanism, driven by a power screw with 12 mm diameter, 4 fillets and 2 mm pitch, was used to generate the elbow flexion and extension movement. The device was able to fully open the fingers, during the tests with a user, in 2.32 seconds and flex or extend the elbow in 4.14 seconds. In addition, the device provided the volunteer with the return of the ability to perform bi-manual activities, became it able to pick up some objects. With the results obtained, it is demonstrated that using these actuators in a robotic orthosis, it is possible that they present an increase in the capacity of health professionals to rehabilitate individuals after stroke.